Gastrointestinal methionine shuttle: Priority handling of precious goods. Issue 12 (17th October 2016) - Mastrototaro, Lucia; Sponder, Gerhard; Saremi, Behnam; Aschenbach, Jörg R.
Abstract: Methionine (Met) is a neutral, sulfur‐containing, essential amino acid with biological functions in the initiation and prolongation step of protein synthesis, transmethylation reactions, the synthesis of cysteine and cystine, and as a component of antioxidant systems. Its key importance is reflected by the fact that it is usually absorbed from the diet with highest efficiency among all proteinogenic amino acids but may yet not optimally support metabolism and health. As such, crystalline Met supplements are partly used in man and heavily used in production of animal species (poultry, fish, shrimps, pigs and cattle) to provide improved health and performance. The main intention of this review is to analyze the current knowledge on transport proteins with proven or hypothetical relevance for Met absorption in the gastrointestinal tract, especially the small intestine. These transporters include Na + ‐dependent B 0 AT1 and ATB 0, + and the Na + ‐independent exchanger b 0, + /rBAT in the apical membrane, which may be supported by the Na + ‐dependent systems ASCT2 and IMINO. The basolateral exit of Met appears to be largely limited to a single uniporter protein, LAT4. Insufficient or overtaxed efflux via LAT4 may lead to significant intracellular accumulation and metabolism of Met in the absorptive state. The latter can release large amounts of homocysteine into the blood, which favors atherosclerosis and other cardiovascular, as well as neurological, diseases. When LAT4 is defective, basolateral Met exit may be compensated to a certain degree by the Met exchange proteins 4F2hc/LAT2 or 4F2hc/LAT1; while carriers 4F2hc/y + LAT1, 4F2hc/y + LAT2, SNAT1 and SNAT2, may serve primarily for basolateral Met import. Expression of SNAT2 is increased when amino acid supply from the lumen ceases, suggesting a key role for Met supply of enterocytes in interdigestive periods. Enterocytes themselves have a huge requirement for Met to synthesize mucins and glutathione. © 2016 IUBMB Life, 68(12):924–934, 2016